Prognostic Value of Skull Base Foramen Invasion Subclassification in T Category Modification and Induction Chemotherapy Management for Nasopharyngeal Carcinoma: Post‐Hoc Analysis of a Dual‐Center Retrospective Cohort Study - Siyu Zhu; Shuqi Li; Di Cao; Chao Luo; Zhiying Liang; Shaobo Liang; Guoyi Zhang; Qin Zhao; Guangying Ruan; Lizhi Liu; Gui Fu; Haojiang Li (Advanced Science)
Abstract Skull base foramen invasion (SBFI) indicates poor prognosis in nasopharyngeal carcinoma (NPC). However, only a few studies systematically assessed the role of SBFIin staging and treatment of NPC. To investigate the prognostic value of SBFI in NPC, a total of 1,752 patients with nonmetastatic NPC from two hospitals (1,320 and 432) between January 2010 and March 2014 are enrolled. The primary endpoint is overall survival (OS). Heatmap/cluster and network analyses are used to provide subclassification indication. Univariate and multivariate analyses with Kaplan–Meier method are performed to compare survival outcomes. SBFIs are classified into slight (only foramen lacerum and/or pterygopalatine fossa invasion) and severe (other SBFIs). The severe SBFI is an unfavorable prognosticator for OS in both the entire cohort and the T3 group. OS is similar between T3 with severe SBFI and T4 patients. Reclassifying T3 with severe SBFI as the T4 category yields an improved T category discrimination. Additionally, patients in the severe SBFI group gain significant survival benefits from induction chemotherapy ((IC). Therefore, T3 NPC with severe SBFI is an independent negative predictor for OS and is classified into the T4 category. T category adjustment enables better prognostic stratification. Severe SBFI benefits from IC in long‐term OS.